First record of Hyalomma rufipes in the Czech Republic, with a review of relevant cases in other parts of Europe - Hubálek, Zdenek; Sedláček, Pavel; Estrada-Peña, Agustín; Vojtíšek, Jakub; Rudolf, Ivo (Ticks and tick-borne diseases, 2020)
We found a male Hyalomma rufipes Koch, 1844 tick feeding on a horse grazing near Valtice, south Moravia, Czech Republic on October 24, 2019. The horse was born in Czechland and did not leave the country at least during the last five years. Relevant findings of Hyalomma ticks in other parts of central Europe are reviewed, including also records of pre-imaginal Hyalomma marginatum complex ticks on migrating birds all over Europe.
Keywords: Hyalomma marginatum; Europe; Česká republika; migrace zvířat; Evropa; mužské pohlaví; rozšíření zvířat; Birds; Czech Republic; Horses; Migratory birds; Horse; zvířata; Ixodidae; koně; Host-Parasite Interactions; Animal Distribution; interakce hostitele a parazita; Central Europe; ptáci; Animal Migration; Male; Czechland; Animals